Digital payments adoption by consumers and firms: Implications for financial inclusion - Razvan Vlaicu (Inter-American Development Bank (IDB), 2025)
Digital payments have increasingly been adopted by consumers and firms in Latin America and the Caribbean. This policy research paper analyzes recent post-pandemic data on digital payments in the region to describe adoption patterns, measure adoption gaps, and identify adoption barriers. The data reveal a positive trend in the use of financial accounts for receiving wages, and of payment apps and digital wallets for purchases in-person and online. Despite increased average adoption, sizable gaps remain both between countries and within countries. At the consumer level, factors associated with delayed adoption include low income, old age, indigenous status, and rural location. At the firm level, factors include small size, retail sector, and limited credit access. Four types of adoption barriers appear to be important: technological, economic, informational, and behavioral. These observations are supported with detailed microdata from Mexico. The paper proposes policy solutions for achieving digital payments inclusion of vulnerable consumers and firms.
Keywords: D18; G23; G50; 330; Digital payments; Adoption gaps; Adoption barriers; Financial inclusion